LINGUISTIC CREATIVITY AND CULTURAL COGNITION IN ENGLISH AND UZBEK FILM AND TV SERIES TTLES: IMPLICATIONS FOR LANGUAGE LEARNING - Ibroximova Sevinch Azizbek qizi,; Ilhomjonova Parvina Zafarovna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation: This article explores the interplay between linguistic creativity and cultural cognition in the titles of English and Uzbek films and TV series. It examines how these elements influence language learning and cultural understanding, providing insights into effective pedagogical strategies for language educators.